2009
DOI: 10.1007/dcr.0b013e31819eb7f0
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and Prognostic Factors for Squamous-Cell Carcinoma of the Anal Canal

Abstract: Although tumor characteristics and staging affect prognosis, patient factors, such as gender, race, and socioeconomic status, are also important prognostic factors for squamous-cell carcinoma of the anal canal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
86
5
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(97 citation statements)
references
References 34 publications
5
86
5
1
Order By: Relevance
“…This controversy in the terms used to describe tumor location was further explored by Wendell-Smith in 2000 [50]. The surgical definition of the anal canal, proposed by the American Joint Committee on Cancer (AJCC), is the most widely accepted [51,52]. By its definition, the anal canal extends from the apex of the anal sphincter complex to the palpable intersphincteric groove at the distal edge of the internal sphincter muscle.…”
Section: Mucosal Terminologymentioning
confidence: 99%
“…This controversy in the terms used to describe tumor location was further explored by Wendell-Smith in 2000 [50]. The surgical definition of the anal canal, proposed by the American Joint Committee on Cancer (AJCC), is the most widely accepted [51,52]. By its definition, the anal canal extends from the apex of the anal sphincter complex to the palpable intersphincteric groove at the distal edge of the internal sphincter muscle.…”
Section: Mucosal Terminologymentioning
confidence: 99%
“…In the US, a study of 38,882 patients with anal cancer found that those undergoing recommended treatment (primary chemoradiotherapy with or without surgery) had an 18% lower risk of death within five years than those who underwent non-guideline treatment [14]. Large singlecentre series have shown similar results.…”
Section: Yorkshire Datamentioning
confidence: 99%
“…Systemic spread is uncommon with distant extra-pelvic metastases reported in 5% to 8% at initial diagnosis. Unfortunately, the prognosis for patients with metastatic disease remains poor with an estimated five-year OS of only 19% (9).…”
Section: Introductionmentioning
confidence: 99%